The effect of endotracheal tube size on voice and swallowing function in patients with thermal burn injury: An evaluation using the Australian Therapy Outcome Measures (AusTOMS). (April 2013) - Cheung, Winston; Clayton, Nicola; Li, Frank; Tan, Jeff; Milliss, David; Thanakrishnan, Govindasamy; Maitz, Peter
Abstract The objective of this study was to determine if intubation using larger endotracheal tube sizes in mechanically ventilated patients with thermal burn injury adversely affects voice and swallowing function. This prospective, observational study was conducted in patients with thermal burn injuries, who were mechanically ventilated via an endotracheal tube. The primary outcome measures were changes in voice and swallowing function, assessed using the Australian Therapy Outcome Measures (AusTOMS), immediately before the burn injury, and 12 months after the removal of the endotracheal tube. Of 101 patients screened, 20 male patients were followed for 12 months. Patients intubated with size 8.0 or larger endotracheal tubes were compared to patients with size 7.5 endotracheal tubes or smaller. Patients with the larger endotracheal tubes had a significant 1.8-point (9%) decline in their AusTOMS voice score (p =.01) using the paired t-test, but there was no significant difference between the two groups using the independent samples t-test. There was no significant difference in swallowing outcome between the two groups. Male patients with thermal burn injuries, mechanically ventilated using size 8.0 endotracheal tubes or larger, had a statistically significant decline in voice outcome; however, interpretation of this result is limited by methodological considerations.